2022
DOI: 10.3390/ijerph19084593
|View full text |Cite
|
Sign up to set email alerts
|

Laser Therapy for the Treatment of Actinic Cheilitis: A Systematic Review

Abstract: Actinic cheilitis (AC) is a chronic inflammation of the lip considered an oral, potentially malignant disorder associated with an increased risk of lip squamous cell carcinoma (SCC) development. Controversies surrounding current therapeutic modalities of AC are under debate, and the implications of laser treatment have not been specifically investigated through a systematic review design. The present study aims to evaluate the degree of evidence of laser for the treatment of AC in terms of efficacy and safety.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…To date, in literature there are only studies that use association of PDT and CO 2 laser therapy for the treatment of these conditions. 3,5 We report the case of two male patients, respectively, aged 73 (patient 1) and 79 (patient 2), presented to our hospital for persistent scaly erythematous-ulcerated plaque of the lower lip (Figure 1A,B) which clinically and dermoscopically suggested the diagnosis of actinic cheilitis. One of them referred to had relapsed after being treated at another center with CO 2 laser only.…”
Section: Combination Of Co 2 Laser Therapy and Pulsed Dye Laser Thera...mentioning
confidence: 94%
See 1 more Smart Citation
“…To date, in literature there are only studies that use association of PDT and CO 2 laser therapy for the treatment of these conditions. 3,5 We report the case of two male patients, respectively, aged 73 (patient 1) and 79 (patient 2), presented to our hospital for persistent scaly erythematous-ulcerated plaque of the lower lip (Figure 1A,B) which clinically and dermoscopically suggested the diagnosis of actinic cheilitis. One of them referred to had relapsed after being treated at another center with CO 2 laser only.…”
Section: Combination Of Co 2 Laser Therapy and Pulsed Dye Laser Thera...mentioning
confidence: 94%
“…Vaporization of intracellular water induced by CO 2 laser acts by local ablation of abnormal epithelium with a good hemostasis of the adjacent structures. 5 FPDL, by emitting a 595 nm wavelength, targets hemoglobin chromophore of vascular structures and may prevent scar hypertrophy. 6 We could confirm that this combined approach is promising, not only for the proved efficacy and good aesthetic outcome, but also for the mini-…”
Section: Combination Of Co 2 Laser Therapy and Pulsed Dye Laser Thera...mentioning
confidence: 99%
“…Nonmelanoma skin cancer (NMSC) accounts for about 95% of skin cancers, mainly including basal cell carcinoma (BCC), squamous cell carcinoma (SCC), extramammary Paget disease (EMPD), and Bowen's disease (2). Over the past decade, the incidence of NMSC has been increasing worldwide to approximately 50-100% (3)(4)(5). A survey showed that the incidence of NMSC in people over 60 years old was 0.64% in China in 2013 (6).…”
Section: Introductionmentioning
confidence: 99%